Cover Image. Issue 3 (17th January 2023) - Terada, K; Yoshizawa, A; Sumiyoshi, S; Rokutan‐Kurata, M; Nakajima, N; Hamaji, M; Sonobe, M; Menju, T; Date, H; Haga, H
Abstract : The cover image is based on the Original Article Clinicopathological features of cytokeratin 5‐positive pulmonary adenocarcinoma by K Terada et al., https://doi.org/10.1111/his.14827 .